Reduction Spermatozoa Motility and Viability on Various Local Chickens During Storage at 5℃ - Hidayat, Nu'man; Hidayah, Chomsiatun Nurul; Nugroho, Aras Prasetiyo (Faculty of Animal Science, Jenderal Soedirman University in associate with Animal Scientist Society of Indonesia (ISPI), 2020)
The research compared the changes motility and viability of sperm from various local chickens during storage at 5℃ for 72 hours. Semen was collected every three days using the dorsal-abdominal massage from twelve chickens consisting of Kedu, Sentul and Pelung chicken. semen was diluted in extender contains 90% lactate ringer and 10% egg yolk extender with 0.025% sodium dodecyl sulfate and 2% vitamin E (LREYSE). Sperm motility and viability was observed every 12 hours and the measurements were made up to 72 hours of storage. Complete random design repeated measurement with 4 replications was used in this study. One-way analysis of variance was used to analyze the data and followed by Duncan’s Multiple Range Test. The results showed sperm motility declined and sperm viability reduced during storage for all breeds. The significant declined of motility between breeds were only observed at 60 and 72 hours and the reduced viability between breeds was observed at 72 hours of storage. The declined sperm motility for Kedu chicken (31.59±3.26% and 75.36±1.25%) and Pelung chicken (36.11±4.05% and 75.83±5.34%) were significantly lower (p<0.05) than Sentul Chicken (50.39±2.60% and 95.00±5.00%) at 60 and 72 hours of storage respectively, while the decline sperm viability of Kedu chicken (57.59±3.64%) and Pelung chicken (54.39±5.73%) was significantly lower (p<0.05) than Sentul Chicken (90.30±9.70%) after 72 hours storage. It can be concluded that the reduction sperm motility and viability of Kedu and Pelung chicken is lower than Sentul chicken which are stored at 5℃ for 72 hours.